Suicide in Manggarai, Eastern Indonesia: Comparative Perspectives from Islamic, Catholic, and Indigenous Law - Fransiska Widyawati; Sumanto Al Qurtuby (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
Suicide is a complex phenomenon that affects individuals and society, demanding global attention and requiring diverse approaches to be fully understood. This article presents a comparative study of suicide, analyzing both its conceptual and practical aspects within the frameworks of Islamic law, Catholic law, and customary law. For the conceptual analysis, a literature review focusing primarily on Islamic and Catholic law was utilized, while for the practical aspects in religious and customary communities, an ethnographic method was utilized. The research reveals both similarities and differences in how Islamic, Catholic, and local customary laws view suicide. All three perspectives condemn suicide as an act that contradicts life and violates their respective legal and moral codes. Although local cultural practices and the religious traditions in Manggarai—including both Christianity and Islam—generally disapprove of suicide, community responses to it vary. Religious approaches tend to be legalistic, individualistic, and moralistic, whereas Manggarai customary law emphasizes a communal, solution-oriented, and harmonious approach. This study contributes to the understanding of interfaith and intercultural perspectives as essential in addressing social issues, including suicide.